ΓENaC/CD9 in urinary extracellular vesicles as a potential biomarker of MR activity. Issue 2 (9th December 2021) - Hayakawa, Tomoaki; Fukuhara, Atsunori; Saiki, Aya; Otsuki, Michio; Shimomura, Iichiro
Abstract : Primary aldosteronism (PA) is caused by autonomous overproduction of aldosterone, which induces organ damage directly via activation of the mineralocorticoid receptor (MR); however, no specific or sensitive biomarkers are able to reflect MR activity. Recently, it is found that urinary extracellular vesicles (uEVs) are secreted by multiple cell types in the kidney and are an enriched source of kidney-specific proteins. Here, we evaluate sodium transporters in uEVs as candidates of biomarkers of MR activity in the clinical setting. Sixteen patients were examined to determine their plasma aldosterone concentration (PAC) and renin activity, and their morning urine was collected. The protein levels of two sodium transporters in uEVs, γ-epithelial sodium channel (γENaC) and thiazide-sensitive sodium chloride cotransporter (NCC), were quantified by Western blot analysis, and their clinical correlation with PAC was determined. Consequently, we found PAC was significantly correlated with the γENaC protein level adjusted by the CD9 protein level in uEVs (correlation coefficient = 0.71). PAC was also correlated with the NCC protein level adjusted by the CD9 protein level in uEVs (correlation coefficient = 0.61). In two PA patients, treatment with an MR antagonist or adrenalectomy reduced γENaC/CD9 in uEVs. In conclusion, γENaC/CD9 in uEVs is a valuable biomarker of MR activity in PA patients and may be a useful biomarker for other MR-associated diseases.